PEMANFAATAAN SISTEM INFORMASI PENGOLAHAN DATA RAWAT INAP PADA RSIA PERMATA BUNDA DENGAN BAHASA PEMROGRAMAN VISUAL BASIC 2010 DAN DATABASE MYSQL - Hendra Nusa Putra, M.Kom anda Tommy Wirawan, M.Kom (Menara Ilmu, 2017)
Computer is an electronic device that are familiar to every human being because as an aid in all things, not only for business applications, education but also can be used in dailyactivities. In the RSIA Permata Bunda inpatient data processing is stil done manualy not usinga computerized system based database. For that the author tries to develop an information system by applying inpatient Visual Basic 2010 Programming Language with MYSQL database. With a system application Visual Basic 2010 programming language and MYSQL as DBMS management, data processing Hospitalized patient at the RSIA Permata Bunda, can beperformed quickly and accurately, and wit the MYSQL database then the security of patientdata on RSIA Permata Bunda can be improved, so the possibility of damaged or missing datais very small.Keywords : Sistem Informasi,Rawat Inap, RSIA, Program, Visual Basic 2010